Effect of recovery interval on multiple-bout sprint cycling performance after acute creatine supplementation - Cottrell, G. T.; Coast, J. R.; Herb, R. A. (The Journal of Strength and Conditioning Research, 2002)
The purpose of this study was to examine the effect of varying recovery intervals on multiple-bout, short-duration, high-intensity cycling efforts of adult men supplemented with creatine (Cr) or a placebo (Pl). Thirty subjects underwent 3 trials of a maximal cycling protocol (T0, T1, T2). T0 included O2max testing and familiarization with the sprint cycling protocol. T1 consisted of 8 15-second bouts of sprint cycling exercise. Subjects were randomly assigned to recovery interval groups (1 minute, 3 minutes, 6 minutes), and Cr or Pl groups (0.3 g·kg1·d1). Posttesting (T2) took place 7 days after T1 and consisted of an identical protocol as during T1. Changes in mean power (MP), peak power (PP), and fatigue index (FI) were compared between trials. MP was significantly increased in Cr 1-minute, Cr 3-minute, and Pl 6-minute groups (p < 0.05). Significant PP increases were demonstrated in Cr 1-minute and Pl 6-minute groups (p < 0.05), and FI significantly increased in Pl 1-minute group (p < 0.05). Results indicate that Cr supplementation is effective in improving recovery from repeated sprint cycling performances when the recovery interval is of a short (<6 minutes) duration.